2012
DOI: 10.1007/s11676-012-0243-7
|View full text |Cite
|
Sign up to set email alerts
|

Purification, characterization and evaluation of insecticidal activity of trypsin inhibitor from Albizia lebbeck seeds

Abstract: A Bowman-Birk inhibitor with activity against gut proteases of Helicoverpa armigera was extracted in 0.1 M sodium phosphate buffer from defatted seed flour of Albizia lebbeck. It was purified to 29.62 folds with 51.43% recovery using ammonium sulfate precipitation, gel filtration chromatography on Sephadex G-100 column and ion exchange chromatography on DEAE-Sephadex A 50 . The purified protein had a molecular weight of 12,303 daltons as determined by SDS-PAGE.It was found to be heat stable up to 60°C and had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 32 publications
0
16
0
1
Order By: Relevance
“…Inhibitors of Kunitz and Bowman-Birk type, isolated from the seeds of Entada acaciifolia and Albizia lebbeck, both belonging to the subfamily Mimosoideae, have molecular weights of 20 and 12.3 kDa, respectively (Oliveira et al 2012, Sharma et al 2012. Based on these results, the inhibitors partially isolated from different species studied include inhibitors of the Kunitz and BowmanBirk type.…”
Section: Discussionmentioning
confidence: 86%
“…Inhibitors of Kunitz and Bowman-Birk type, isolated from the seeds of Entada acaciifolia and Albizia lebbeck, both belonging to the subfamily Mimosoideae, have molecular weights of 20 and 12.3 kDa, respectively (Oliveira et al 2012, Sharma et al 2012. Based on these results, the inhibitors partially isolated from different species studied include inhibitors of the Kunitz and BowmanBirk type.…”
Section: Discussionmentioning
confidence: 86%
“…The noncompetitive mechanism found for the inhibition of ApTI on the trypsin‐like enzymes of A. gemmatalis agrees with other in silico studies carried out with trypsins from other species of the order Lepidoptera (Migliolo et al, 2010; Ramalho et al, 2018), and the reactive (inhibitory) peptide bond was identified in the alpha chain with the participation of the Arg64 residue and amino acid residues around Pro63, Ile65, and Arg66. This bond is at an exactly homologous position to the reactive sites identified in the soybean inhibitor at Arg‐63‐Ile‐64 (McPherson, Daym, & Larson, 2019) in Albizia at Arg‐66‐I1e‐67 (Sharma, Nath, Kumari, & Bhardwaj, 2012) and in Psophocarpus at Arg‐64‐Ser‐65 (Yamamoto, Hara, & Ikenaka, 1983).…”
Section: Discussionmentioning
confidence: 82%
“…On the other hand, proteinase inhibitors are potential candidates for biocontrol of insect pests since insect digestive proteinases are promising targets towards control of various insects (Sharma et al, 2012). Proteases have been found to be effective against many Coleopteran (Elden, 2000).…”
Section: Resultsmentioning
confidence: 99%